Analysis of Facility and Safety Management Implementation for Hazardous Materials at Hospital X - Maria Saraswati Kinasih Hapsari; Raden Bonifacius Bayu Erlangga Kusuma; Anggit Wirama Siwidati (Universitas Airlangga, 2025)
Background: The management of hazardous and toxic materials is an essential component of Hospital Occupational Safety and Health standards. In addition, it is included in the Hospital Accreditation Standards, specifically in Facility and Safety Management Standard No. 5. However, in practice, some hospitals—including Hospital X—still do not meet these requirements. Objectives: This study aims to evaluate the implementation of facility and safety management standard elements related to hazardous and toxic materials at Hospital X in order to provide appropriate recommendations for improvement. Methods: This study employed a descriptive observational design. Data were collected through observations and interviews with relevant staff across 15 service units assessed against the facility and safety management standard elements for hazardous and toxic materials, as outlined in the Ministry of Health Regulation No. HK.01.07/MENKES/1596/2024. The study was conducted from June to August 2025 at Hospital X. Results: Service units that met the facility and safety management standard elements for hazardous and toxic materials (>80%) included radiology (87.50%), hemodialysis (95.65%), pharmacy (95.65%), laundry (95.65%), Occupational Safety and Health (OSH) & sanitation (95.65%), emergency department (91.30%), central surgical unit (91.20%), and Intensive Care Unit (ICU) (91.30%). Units that did not meet the standard elements (<80%) were nutrition (39.13%), laboratory (65.21%), inpatient care (60.86%), outpatient care (65.21%), forensic (60.86%), medical rehabilitation (34.78%), and IPSRS (34.78%). Conclusion: Only 8 out of 15 service units met the facility and safety management standard elements for hazardous and toxic materials. Therefore, improvement efforts should prioritize the provision of MSDS, proper material inventory recording, classification-based labeling, and chemical segregation according to their characteristics.